Swot analysis of factors causing air pollution and recommended control efforts in the city of Yogyakarta, Indonesia - Naris Dyah Prasetyawati; Suranto Tjiptowibisono; Pranoto Pranoto; Sunarto Sunarto (Environmental Health Engineering and Management, 2024)
Background: Knowing the root causes of air pollution in urban areas will determine the next actions to take. Analyzing the impact caused by air pollution will make it easier to determine the control efforts to be carried out. Determining control objectives makes the efforts more targeted. Air pollution can be controlled through abiotic, biotic, and cultural factors. Methods: Primary data collection was carried out and used secondary data. This study aimed to find the causes of air pollution in urban areas using the strengths, weaknesses, opportunities, and threats analysis method so that it can see what efforts are appropriate to do. Results: It was revealed that the government’s efforts to control air pollution have been carried out continuously and in multi-sectoral ways, but the socialization of the impact of air pollution has not been conveyed to the community continuously and has not been on target. Conclusion: Noise and dust are still the main problems affecting air quality in urban areas. Another problem is in human behavior as an affected and interested party. The potential for controlling air pollution can be carried out by combining the strengths and opportunities that are owned optimally and multi-sectorally.